Integrated assessment quality of life and exercise performance in adults after pulmonary autograft operation - I. Lebid; A. Razinkina; А. Sydorenko; Y. Klymyshyn; A. Romanyuk; Ye. Liebied; V. Khanenova; N. Rudenko (Ukrainian Journal of Cardiovascular Surgery, 2017)
Patients after Pulmonary Autograft Operation (PAO) have good follow-up in the early postoperative period, but late postoperative period require further examination.The purpose of the work was to assess quality of life (QoL) and exercise performance (EP) in adults after PAO.Material and methods. From 01 Jan. to 31 Dec 2016 there were examined 46 consecutive adults elder 18 years. Gr. A (n=22) patients after PAO (Gr. A1 n=8 with NYHA I, Gr. A2 n=14 with NYHA II–III), Gr. B (n=24) healthy adults.Results. In Gr. A mean age 21.6±0.8 years (from 18 to 30 years), male (n=14; 63.6%), Gr. B – 22.7±1.3 years (from 18 to 28 years), male (n=14; 58.3%). Test 6MWT (Gr. A 429.6±22.2 m, Gr. B 593.3±7.6 m, p<0.01; Gr. A1 533.8±26.7 m, Gr. A2 377.1±20.6 m, p<0.01). Second stage Systolic BP (Gr. A1 153.8±6.0; Gr. A2 150.4±5.8 mmHg, Gr. B 139.8±3.3, p<0,05). PWC170 in Gr. A2 (745.7±72.2 kgm/min), Gr. A1 (1035.0±82.6 kgm/min, p<0,05) and Gr. B (1041.4±82.5 kgm/min p<0.05, p<0.01). Vo2 in Gr. A2 (2.5±0.1 l/min), Gr. B (3.0±0.1 l/min, p<0.05). In Gr. A2 gradients on PA conduit were (37.8±6.1), Gr. A1 (27.3±4.8, p<0.05) and in Gr. B (8.1±3.1, p<0.01). Indexes of QoL were in Gr. A2 PF (78.6±5.0), BP (66.0±6.9), GH (59.8±5.7) and SF (70.5±6.5), in Gr. A1 PF (83.1±4.0) were worse compare with Gr. B (94.2±1.6; 81.3±4.8; 75.0±4.4; 85.4±3.4, respectively, p<0,05).Conclusions. All patients after PAO are necessary to study exercise performance using the proposed method. Low EP and QoL in late follow up period in these patients characterized by low indexes of PWC170, Vo2 max as the result of additional re-procedures, higher PA conduit gradients and decreasing of RV function.